FROM AN ALLERGIC REACTION TO A SUPERIOR VENA CAVA SYNDROME - Milutinović, Vojislava (Halo 194 Scientific Journal of Emergency Medicine, 2024)
AbstractIntroduction: Superior vena cava syndrome ( SVCS) is a collection of clinical signs and symptoms resulting from partial or complete obstruction of blood flow through the SVC.  Case report: An eighty-year-old patient with an allergy diagnosis was referred from the Community Health Centre to the Internal Medicine Clinic. The patient had previously been treated with antihistamines for days due to swelling and facial redness, which showed no signs of improvement. During the chest x-ray, a widened shadow of the upper side of the mediastinum on the right side was noticed.  A CT chest scan showed an infiltrative change and a significantly compressed upper vena cava due to the mediastinal adenopathy. Conclusion: If primarily manifested by skin symptoms, the diagnosis of superior vena cava syndrome can be easily overlooked. In the presented case, this rare syndrome was the first symptom  of intrathoracic malignancy.
Keywords: superior vena cava syndrome, allergy, urgent radiotherapy